Análise da evapotranspiração por meio de Wavelets em uma Floresta de Vochysia divergens no Pantanal - Goulart, Milena Athie (2012)
The temporal-spatial variation of evapotranspiration was analyzed by means of a wavelet in Vochysia divergens forest (locally known as Cambarazal) Private Reserve Heritage National SESC Pantanal, municipality of Barão do Melgaço, Mato Grosso, Brazil. This area is inserted in the Pantanal plain physiographic and is seasonally flooded. The data of net radiation, solar radiation, air temperature, relative humidity and wind speed were collected by sensors installed in a micrometeorological tower at 32 m height. Flows of latent and sensible heat were estimated from the energy balance at the earth surface. To characterize the partition of the available energy from the records of the gradients of temperature and vapor pressure above the evaporating surface was used Bowen ratio (B). The analysis of time series of the energy flows was performed using wavelet. The results indicate significant power spectral peaks in the range of hourly and daily temperature and relative humidity corresponding to the months April to September, this is because the relative humidity depends on the temperature of the hotter is the air, the vapor water it can hold. During June and August months are the period of drought, it was noted that when the solar radiation decreased, so did the evapotranspiration, indicating a relationship between these two variables. In this period there was dried evaporation amount of less than in the wet season, probably because the canopy may be functioning as a kind of gases, thereby contributing to the solar radiation stayed longer retained on the surface, as well as particulate matter in the atmosphere . The maximum value of vapor pressure deficit of air occurred during the dry season. The analysis of hourly and daily time series by wavelet year was satisfactory enabling a better understanding of the dynamics of evapotranspiration in flooded area.